Isu Global Marketing Pendidikan dan Entrepreneurship Pendidikan WCE (Pondok Pesantren Al-Ashriyyah Nurul Iman Islamic Boarding School) - Pertiwi, Getar Rahmi; Latief, Mukhtar; Anwar, Kasful (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2024)
The globalization of educational development through science and technology in the current era is moving so fast and great. Moreover, with the presence of the industrial revolution era 4.0 and welcoming the era of society 5.0. Globally, education on an international scale is generally based on the concept of enriching knowledge, honing independence and developing students' soft and hard skills. Likewise, with Islamic boarding schools, with their independence, they will become autonomous educational institutions, both from the learning system and funding. So how Islamic boarding schools manage their finances, including the strategies used to raise funds to continue the educational process in Islamic boarding schools. In the early stages of education in Islamic boarding schools, it was focused solely on teaching religious knowledge through classical books or the yellow book. Religious sciences consisting of various branches are taught in Islamic boarding schools in the form of wetonan, sorogan, memorization, or muzakarah. However, after the introduction of the ideas of reforming Islamic thought to Indonesia, this also influenced changes in the Islamic education system in Islamic boarding schools. Islamic boarding school education, which was initially only oriented towards deepening religious knowledge, began to include general subjects. It is hoped that the inclusion of general subjects will broaden the thinking horizons of the students and better prepare the students to face developments in the times.